Psychosocial Intervention through Exercise and Gardening for People with Mental Disorders at UPTD Liposos Jember - Mansur, Ahmad Ali; Suharto, Adelia Sabina; Nadhira, Aulia; Rosidah, Chilmiyatur; Sabila, Fianda Azza; Darmaningtyas, Jihan; Santi, Maharani Puspa; Wardhani, Sheilla Kusuma; Nugroho, Sheilomitha Anjani; ‘Aini, Tazqia Qurrota; Ririanty, Mury (Jurnal Pengabdian Masyarakat, 2025)
Purpose: This study evaluates the effectiveness of psychosocial interventions through exercise and gardening for individuals with mental disorders at UPTD Liposos Jember, addressing the high prevalence of mental health issues in the region and the need for sustainable, non-pharmacological rehabilitation. Method: A qualitative approach was employed from April to June 2025, involving rhythmic exercise and polybag gardening. Daily observations and documentation assessed behavioral changes, engagement, and social interaction among 35 participants. Practical Applications: Findings support integrating these activities into Individual Care Plans and rehabilitation curricula, enhancing patient motivation, social skills, and emotional well-being. The program also serves as training for caregivers and a model for community-based mental health services. Conclusion: Exercise and gardening significantly improved participants’ physical, mental, and social well-being, with facilitator involvement being key to success. Integration into routine care is recommended for long-term impact.